This is an arithmetic sequence.
The numbers differ by a constant.
The general form of an arithmetic sequence is:
![a_n=a+(n-1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/t99kk5roieipg56xa37yseewl9ybc4zh6i.png)
Where
a is first term
n is nth term
d is the common difference
Looking at the sequence, we can say the common difference is -3 [since 3 is subtracted from a term to get the next term]
Also, first term is 13
Now, we plug into formula:
![\begin{gathered} a_n=a+(n-1)d \\ a_n=13+(n-1)(-3) \\ a_n=13-3n+3_{} \\ a_n=16-3n \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sy7l3m0nqc61grqda8nffkzu2na87xrtaj.png)